Production, physiological response, and calcium and magnesium balance of lactating Holstein cows fed different sources of supplemental magnesium with or without ruminal buffer - Lobo, Richard Roberto (2023)
The objective of this study was to evaluate the effects of dietary replacement of magnesium oxide (MgO) with calcium-magnesium hydroxide [CaMg(OH)2] and its interaction with ruminal buffer (sodium sesquicarbonate) supplementation on production, Ca and Mg balance, and overall physiological response of mid-lactation Holstein dairy cows. Sixty cows averaging 40.5 ± 7.0 kg of milk/d were used. Treatments were assigned following a 2 × 2 factorial arrangement: (1) MgO, (2) MgO + buffer, (3) CaMg(OH)2, or (4) CaMg(OH)2 + buffer. Diets were formulated to have 16.5% of crude protein, 1.82 Mcal/kg of net energy for lactation, 0.67% Ca, 0.39% P, and 0.25% Mg, all on a dry matter (DM) basis. Treatments were individually top dressed. Milk production, composition, and DM intake were evaluated. A subsample of 20 cows were randomly selected for the evaluation of Ca and Mg balance, blood gases, and electrolytes. Ruminal fluid was also collected for evaluation of pH and Ca and Mg solubility. Effects of Mg source, buffer, and the interaction Mg source × buffer were analyzed through orthogonal contrasts. An interaction of Mg source × buffer was found for DM intake and feed efficiency, in which cows fed CaMg(OH)2 had a similar feed efficiency regardless of ruminal buffer inclusion; however, when cows were fed MgO, the inclusion of buffer reduced feed efficiency. No effects on body weight and milk yield were observed. Buffer addition tended to increase the concentrations of fat, protein, and solids-not-fat, without affecting the yields of these milk components. Magnesium source and buffer did not affect ruminal fluid, blood, urine, or fecal pH; however, buffer supplementation increased urinary pH. Treatment with CaMg(OH)2 increased blood concentration of HCO3 −, total CO2, and base excess compared with cows fed MgO. No differences were observed in the ruminal solubility of Ca and Mg or on milk or urinary Ca and Mg excretion. Greater plasma Mg concentration was observed for animals fed MgO compared with cows fed CaMg(OH)2; however, both sources were above the threshold recommended in the literature for dairy cows. Also, a reduction in fecal Mg excretion was observed in animals fed CaMg(OH)2. In summary, we provide evidence that CaMg(OH)2 could replace MgO without affecting performance, overall physiological response, or Ca and Mg balance of mid-lactating dairy Holstein cows.